(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: The integration of technology into the operations of micro enterprises has become a critical factor in enhancing business performance, especially in the context of business growth. However, the empirical effect of AI-driven technological integration on micro enterprises in Osun State, Nigeria, remains underexplored. This study therefore examined how AI-enabled technological tools affect micro enterprise performance within the state. A survey research design was employed, covering 30 Local Government Areas (LGAs) and the Modakeke-Ife Area Office, with a study population of 288,780 micro business owners across various sectors who have created paid jobs for others (NBS, 2017). A sample size of 400 was determined using Taro Yamane's formula. Data were collected through a structured questionnaire and analysed using SPSS version 25, utilising both descriptive statistics (frequencies and percentages) and multiple regression analyses. The findings indicate that digital skills (0.795), digital infrastructure (0.724), and e-commerce platforms (0.692), when powered by AI technologies, significantly affect business growth among micro entrepreneurs. Collectively, these factors account for 78.4% of the variance in business growth. The study concludes that AI-driven technological integration is a key driver of micro enterprise performance and employment. It is recommended that policymakers and stakeholders focus on improving AI-enabled digital infrastructure, enhancing digital literacy, and supporting intelligent e-commerce adoption to boost micro enterprise growth and job creation in Osun State.